Performance evaluation of GaroleÃ—Malpura half-bred sheep evolved in semiarid - MISHRA, A K; ARORA, A L; PRINCE, L L L; KUMAR, SATISH (The Indian Journal of Animal Sciences, 2011)
Performance of newly evolved Garole×Malpura (GM) half-breds was evaluated using data from 2002 to 2006 (5 years). The overall least squares means of body weights at birth, weaning, 6 and 12 months of age were 1.94±0.04, 9.84±0.26, and 14.48±0.39 and 20.42±0.79 kg, respectively. Significant effects of type of lambing were observed on the body weights. The body weights of single born lambs were relatively higher than those of twins and triplets. GM lambs (294) were selected randomly and screened for FecB mutation using forced RFLP-PCR technique. The majority (73.81%) of GM individuals were carriers (BB and B+) for the FecB mutation. The FecB genotypes were significantly associated with the lamb’s body weights from birth to 12 months of age and the body weight of FecB carrier lambs were lighter than non-carriers. The lambing rate averaged 143.50% in GM ewes. The twin lambing percentage was only 4.71% in Malpura flock; it had reached up to 47.02% in GM; 6.55% of available GM ewes produced triplets also. The results revealed that the fecundity genes responsible for increasing litter size have been incorporated into the GM genotype and it might prove a valuable germplasm towards evolving a new prolific strain of sheep.